Calculation of contraction patterns in rat skin flap model - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
Introduction: In this study rat abdominal skin flaps were observed daily to explain their contraction behavior and a mathematical formula has been developed. Methods: 24 male rats were used for the study. Abdominal skin flaps based on the inferior epigastric neurovascular bundles were raised. In the first group all flaps were sutured to their donor area without any extra physical or chemical interference. In the second groups steroid was applied under the flaps to change the contraction rate. Results: Contraction rate was significantly higher in necrotic tissues in both groups. A formula was used to correct for the contraction. The corrected results for the seventh day necrotic area percentage measurements were significantly higher than actual measurements. (p = 0.0001). Conclusions: By using the mathematical formula developed in this study, pre-contraction value of the experimental skin flaps can be achieved and the results can be interpreted more accurately.
Keywords: Rat; epigastric flap; flap contraction; WOUND CONTRACTION; MYOFIBROBLAST; DEXAMETHASONE; ISCHEMIA